Insight on Estrogen Receptor Alpha Modulator from Indonesian Herbal Database: An in-silico analysis - Muhammad Arba; Nadhifatul Aslikah; Arfan Arfan; Ruslin Ruslin; Arry Yanuar (Pharmacy Faculty, Universitas Muhammadiyah Purwokerto, 2020)
Estrogen receptor α (ERα) is liable for regulating transcription factors which are an important part of hormonal signaling in breast cancer. This study intends to find hit compounds that are considered capable of inhibiting ERα by utilizing structure-based pharmacophores and molecular docking. Pharmacophore of the original ERα ligand (E4D600) has one hydrogen bond acceptor and three hydrogen bond donors which are used to select compounds from the Indonesian herbal database. This pharmacophore model had an Area under Curve of the Receiver Operating Characteristics (AUC-ROC) value is 0.80 and the Goodness of Hits (GH) value is 0.81. The selection process generated 330 compounds which proceed to the molecular docking stage to analyze their binding energy and interactions to ERα. The results indicated potential hit compounds seen from their binding energies in the range -5.42 to -10.01 kcal/mol. four of the best compounds including Lig57/(-)-Bidwillon A, Lig47/Quercetin 3-(6''-galloylgalactoside), Lig197/Multifloroside and Lig83/Erythrabyssin II provide promising information for their detailed analysis as ERα inhibitors.